сначала раскладываем выражение по формуле квадрата разности, потом приводим подобные слагаесые:
(а - в)² = а² - 2ав + в²,
36в² - (6 - в)² =
= 36в² - (36 - 12в + в²) =
= 36в² - 36 + 12в - в² =
= 35в² + 12в - 36
ответ: 36b^2-36+12b-b^2=0
35b^2 +12b-36=0
D=(-12-+144+4*35*36)/70
b1=-12-72/70=1,2
b2=-12+72/70=6/7
Пошаговое объяснение:
сначала раскладываем выражение по формуле квадрата разности, потом приводим подобные слагаесые:
(а - в)² = а² - 2ав + в²,
36в² - (6 - в)² =
= 36в² - (36 - 12в + в²) =
= 36в² - 36 + 12в - в² =
= 35в² + 12в - 36
ответ: 36b^2-36+12b-b^2=0
35b^2 +12b-36=0
D=(-12-+144+4*35*36)/70
b1=-12-72/70=1,2
b2=-12+72/70=6/7
Пошаговое объяснение: